MENGEMBARA KE NEGERI SURAM: TELAAH NOVEL "SARONGGE" KARYA TOSCA SANTOSO - Kafrawi, Muhammad (Jurnal Ilmu Budaya, 2016)
In indonesia, the problem about forest is usual because th.is countty has natural rasources I ike forest which spread from sabang to marauke. More over, forest is one of important elements in humans lives. Related to it, this writing deals with an analysis of a literary work entitles "Sarongge" which tells about an enviromental activist who gives everything to save forest, who strunggles and.fight to keep the forest.